Impact of multi-frequency ultrasound processing with different treatment times on the structural quality of frozen wheat dough - Zahoor Ahmed; Bin Xu; Umar Farooq; Muhammad Faisal Manzoor; Mohamed F. Awad; Jawad Ashraf; Tabussam Tufail; Gholamreza Abdi (Ultrasonics Sonochemistry)
This study investigates the effects of multi-frequency ultrasound treatment on the quality of frozen dough. We analyzed frozen wheat dough comprehensively for texture, viscosity, rheology, and structural quality characteristics under multi-frequency ultrasound (20 kHz, 20/40 kHz, and 20/40/60 kHz) with different treatment times (10, 20, and 30 mins). The dough treated with multi-frequency ultrasound increased elasticity and reduced hardness. Scanning electron microscopy revealed that 20/40/60 kHz for 30 min minimized freezing-induced morphological damage, decreased the tan δ in rheological analysis, and led to higher pasting and gelatinization enthalpy in starch granules, resulting in a more cohesive structure and lower free water content. Frozen dough hardness decreased by 52.1 %, which is associated with the control frozen dough with ultrasound frequency and duration changes. The spectral peaks in wheat flour frozen dough treated with single, dual, and tri-frequency ultrasound had the same forms and positions as the control samples but were arranged in an orderly manner. This study demonstrates the potential of multi-frequency ultrasound to enhance the quality of wheat frozen dough by mitigating freezing-induced deteriorations, offering a promising approach to improving the processing of frozen dough.